تصريف الفعل ودلالات اختلافه في القراءات القرآنية - بله باسي, بسمة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى معالجة قضية اختلاف تصريف الفعل حول الزمن من جهة، وحروف المضارعة من جهة أخرى ودلالته في القراءات القرآنية، وذلك باستهداف مواقع الخلاف في تصريف الفعل بين القراء العشرة وتوجيه أهل التفسير وعلماء الصرف واللغة لها، وبيان أوجه تأثير هذا الاختلاف على المعنى ودلالات هذا التنوع، وهل يقتصر هذا التغاير على اللفظ أم يتعداه إلى المعنى؟ وهل تستوجب الزيادة في المبنى زيادة في المعنى؟ ومن ذلك نصل إلى وجود تنوع صيغي بين أزمنة الفعل ماضية ومضارعة وأمرا، بالإضافة إلى الاختلاف حول حروف المضارعة وهو مصحوب بتغيرات دلالية، وهذا الاختلاف الدلالي من قراءة إلى أخرى ليس اختلاف تناقض وإنّما هو اختلاف تنوع في الفهم أو المعنى بما يزيد من وضوح المراد. This study aims to examine the issue of the difference in the conjugation of the verb around tense on the one hand, and the present tense endings on the other hand, and its significance in the Qur’anic recitations, by targeting the different perspectives on the conjugation of the verb among the ten recitations, Ahl Tafsir morphologists and linguists. The study aims at clarifying the difference in terms of its impact of the semantic and pragmatic meanings and to examine whether the difference in recitations is confined to utterances or extended at the meaning level and does this requires morphological affixations?We conclude that the existence of morphological diversity of the tense aspect of verb the past, present, and command, in addition to the difference in the present tense affixations and it is accompanied by changes in the semantic connotations.This semantic difference from one recitation to another is not contradictory, but rather it is due to a difference in interpretions that add the needed clarity.
مقال
Keywords: تصريف الفعل؛ زمن الفعل؛ حروف المضارعة؛ دلالة الاختلاف؛ القراءات القرآنية; (verb conjugation; verb tense; present tense letters; difference indication; Quranic readings)